Post-truth or agnogenesis? Theorizing risk and uncertainty in a neoliberal nature. Issue 8 (3rd August 2019) - Martyn, Kevin P.; Bosman, M. Martin
Abstract: In the aftermath of the great recession, many have investigated the characteristics of life in a 'neoliberal nature'. In more recent months, we have also seen an apparent erosion of truth, the 'post-truth' moment. This paper argues that there are important and undertheorized links between the risk centrality of life in neoliberal nature and the post-truth moment. We begin by reviewing some treatments of risk from different fields, coming to the general conclusion that neoliberal nature is a place characterized primarily by its heightened risk(s). We then undertake a Foucauldian interpretation of neoliberal governmentality to demonstrate that the strategy of recasting society as atomized agents of risk is the source of a great deal of alienation and discontent, manifesting in an apparently post-truth citizen/society relationship. Next, we relate each of these concepts to the study of culturally induced ignorance, or 'agnotology, ' to demonstrate that neoliberal governmentality in fact requires the systemic production of ignorance. We then propose an extension of agnotology to argue that a seemingly innocuous post-truth moment is better understood as an outgrowth of the deliberate production of targeted ignorance, especially in the context of environmental injustices. Finally, to provide an illustration of the trends described in this paper, we conclude with a section on the historic use of leaded gasoline in the U.S.